Types of local anesthetic (Journal of Science-Innovative Research in Uzbekistan, 2023)
This exploration delves into the diverse landscape of local anesthetics, shedding light on the various types that play a crucial role in pain management during medical procedures. From lidocaine to bupivacaine, this article navigates through the mechanisms, applications, and considerations associated with different classes of local anesthetics. Understanding the distinctions and optimal usage of these agents is vital for healthcare professionals in ensuring effective and safe pain relief for patients